Airborne Particulate Sampling using Direct Reading Instruments around Frac Sand Facilities - Kentnich, Jacob; Keenan, Ella; Pierce, Crispin (My University, 2017)
The goal of our research is to identify any possible acute or chronic health outcomes from the inhalation of frac sand particulates. There are currently 135 sites in the state of Wisconsin collectively mining 30 million tons of sand per year. Comparisons are made with the Department of Natural Resources (DNR) database on daily air quality to determine if the quality of air is of difference around frac sand facilities. On average, PM2.5 should not exceed a level of 12 micrograms per cubic meter. Our average of 55 samples of PM2.5 readings was 10.73 micrograms per cubic meter with a standard deviation of 0.0114 (range 1-63). Every 6 days, we use the DustTrak II to sample air near the frac sand mine in Bloomer, WI. This cycle is consistent with the Environmental Protection Agency’s (EPA) 6-day sampling schedule. We study particulate matter that is of 2.5 microns of size (PM2.5) because these microscopic particles embed themselves deep in the lung tissue. Frac sand, also known as silica sand, is a known human carcinogen, which can lead to lung cancer and silicosis. We use a direct reading instrument, the DustTrak II, to monitor the ambient air quality of communities that are susceptible to frac sand dust.
Color poster with text, charts, maps. images and graphs.
Keywords: Hydraulic fracturing; Frac sand; Sand mining; Airborne pollutants; Posters